Implementasi Program Peningkatan Perilaku Pemilahan Sampah Rumah Tangga, Revitalisasiâ€œSmart Waste Managementâ€, Dan Konversi â€œWaste To Energyâ€ Di Kota Bekasi - Saputra, Ricky Febri; Hidayat, Rahmat; Nababan, Rudyk (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2021)
In dealing with waste management problems in Bekasi City, the Bekasi City Government has implemented waste management innovations by involving the community's role through the Program for Improvement of Household Waste Segregation Behavior, Revitalization of